2021
DOI: 10.3390/atmos12111384
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of the Thermosphere and the Ionosphere during a Meteorological Storm

Abstract: Determination of the physical mechanisms of energy transfer of tropospheric disturbances to the ionosphere is one of the fundamental problems of atmospheric physics. This article presents the results of observations carried out using two-wavelength lidar sensing at tropospheric altitudes and satellite GPS measurements during a meteorological storm in Kaliningrad (Russia, 54.7° N, 20.5° E) on 1 April 2016. During lidar sensing, it was found that the amplitudes of variations in atmospheric parameters with period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…This observation implies that the propagation of TIDs is driven at all the phases of geomagnetic storms which suggests that the behavior is complicated and perhaps is sometimes driven by meteorological phenomenon other than substorms. We suspect that the influence of magnetospheric substorms and meteorological factors could be responsible for the generation of TIDs occurrence at initial, main and recovery phases of geomagnetic storm (Borchevkina et al., 2021; Meng, Tsurutani, & Mannucci, 2019).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation implies that the propagation of TIDs is driven at all the phases of geomagnetic storms which suggests that the behavior is complicated and perhaps is sometimes driven by meteorological phenomenon other than substorms. We suspect that the influence of magnetospheric substorms and meteorological factors could be responsible for the generation of TIDs occurrence at initial, main and recovery phases of geomagnetic storm (Borchevkina et al., 2021; Meng, Tsurutani, & Mannucci, 2019).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Meteorological/geological events such as thunderstorm, sudden stratospheric warming, volcanos, tsunamis, underground nuclear explosion, typhoon, earthquakes propagate medium‐scale traveling ionospheric disturbances (MSTIDs) (Artru et al., 2005; de Jesus et al., 2017; Jonah et al., 2020; Kundu et al., 2021; Maletckii & Astafyeva, 2021; Meng, Vergados, et al., 2019; Occhipinti et al., 2013; Sunil et al., 2015). For instance, findings on thunderstorm have shown that the activities of lighting produced during thunderstorms can transfer energy from the troposphere through gravity waves and infrasonic waves to the region of the ionosphere (Borchevkina et al., 2021; Freeshah et al., 2020; Mohannakumar, 2008; Ogunsua et al., 2020; Sindelarova et al., 2009). These studies have unveiled the connections between the lower atmospheric layers and the ionosphere (troposphere‐stratosphere‐ionosphere coupling).…”
Section: Introductionmentioning
confidence: 99%
“…The low‐frequency wave tend to propagate to a far place, while high‐frequency wave tend to propagate upward (Kong et al., 2017; Xiao, Hao, et al., 2006, Xiao, Zhang, & Xiao, 2006). Some theoretical calculations show that the AGW generate by strong meteorological activity can spread out in concentric circles and can affect the structure of the atmosphere (Borchevkina et al., 2021; Vadas & Azeem, 2021). This phenomenon has been confirmed by observation (Chou, Lin, Yue, Tsai, et al., 2017; Chou, Lin, Yue, Chang, et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Methane can penetrate into the stratosphere via turbulent diffusion from the troposphere to the stratosphere and sequentially to the mesosphere and ionosphere during tropical hurricanes, thunderstorms, and volcanic eruptions [2,3]. This transport process can be significantly enhanced by the propagation of internal and acoustic gravity waves (IGWs and AGWs) [4][5][6]. In the polar latitudes, troposphere gases can also be transported to the upper atmospheric layers through the polar vortex [7].…”
Section: Introductionmentioning
confidence: 99%